2019
DOI: 10.1111/aogs.13749
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a comorbidity index for use in obstetric patients: A nationwide cohort study

Abstract: Introduction A previously developed Obstetric Comorbidity Index has been validated in highly selected cohorts. Validation of the index in an unselected population as well as in other health registers is, however, of high importance to determine external validity. Material and methods Using nationwide registers, we formed a nationwide cohort including completed pregnancies (both live‐ and stillborn) in Denmark from 2000 through 2014. Maternal age and 20 comorbid conditions were assessed and weighted. Outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Three studies conducted in Canada, Denmark, and the United States each used the obstetric comorbidity index retrospectively in huge sample sizes. All had consistent findings of an increased risk of severe maternal outcomes with every one-point increase in the obstetric comorbidity index [59][60][61]. A study conducted in Canada found that the presence of major preexisting conditions increased women's risk of SMM six-fold [62].…”
Section: Plos Onementioning
confidence: 69%
See 1 more Smart Citation
“…Three studies conducted in Canada, Denmark, and the United States each used the obstetric comorbidity index retrospectively in huge sample sizes. All had consistent findings of an increased risk of severe maternal outcomes with every one-point increase in the obstetric comorbidity index [59][60][61]. A study conducted in Canada found that the presence of major preexisting conditions increased women's risk of SMM six-fold [62].…”
Section: Plos Onementioning
confidence: 69%
“…These were similar to that of the current study. Studies in Canada and Denmark using the same obstetric comorbidity index showed areas under the curve of 64% [59] and 70% [61]. In Turkey, where the Knox scoring system was used, the area under the curve on admission was 65%, while at the onset of labor, it was 94% [45].…”
Section: Plos Onementioning
confidence: 99%
“…The presence of comorbid conditions which might confound the association between pregnancy status and outcome were identified by adaptation of a validated obstetricspecific comorbidity index to exclude obstetric-specific comorbid conditions (e.g., preeclampsia), and by adjustment of criteria developed for an international version of ICD-10 for the United States implementation. 9,10 Diagnosis and procedural coding were similarly used to identify potential indications for ECMO deployment (such as acute respiratory distress syndrome, heart failure, pulmonary hypertension, and amniotic fluid embolism). Outcomes analyzed included in-hospital mortality from index hospital stay, length of stay, total estimated hospital charges and costs and an occurrence of thromboembolic or bleeding complication.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The tool was validated in a prospective study by Easter et al1 which confirmed that the higher the score the greater the association with need for ICU level care. Two other recent studies were cited from Denmark2 and the United States3 which further confirmed the validity of OB-CMI as an excellent tool to predict maternal morbidity and mortality.…”
mentioning
confidence: 59%